PROPOSED DESIGN OF STRATEGIC SOURCING AND PRODUCTION BOTTLENECK MANAGEMENT FOR REVENUE MAXIMIZATION: AN OPERATIONAL PERFORMANCE ANALYSIS OF PT. ELSEWEDY ELECTRIC INDONESIA - Agung Sukma Hardana; Dermawan Wibisono (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
This study aims to analyze strategic sourcing and production bottleneck management to maximize revenue of PT. Elsewedy Electric Indonesia. The company faces challenges in meeting increasing market demand, especially in the renewable energy sector. The company's main challenge is the mismatch between current production capacity, which is optimized for medium to high capacity transformers, and market demand that is shifting towards smaller transformers. This study uses qualitative and quantitative approaches. Qualitative data were collected through semi-structured interviews with five stakeholder: (1) General Manager, (2) Head of Production, (3) Production Manager and (4) Sourcing Manager from PT. EEI. Quantitative data include historical production data, cycle time data from MOST (Maynard Operation Sequence Technique) studies, and actual machine or workspace data. SWOT analysis is used to map sourcing strategies, and MOST studies are used to calculate production cycle time and plant capacity. The Balanced Scorecard (BSC) is implemented to align operational performance with long-term financial targets. The Balance Scorecard covers four perspectives, namely financial, customer, internal process, and learning & growth, with a total of 10 strategic objectives. The research findings show that the Dry Oven and testing stages are bottlenecks in the production process. The maximum monthly capacity is 14 units or equivalent to 840 MVA, while the winding process can produce 19 units or equivalent to 1140 MVA. Strategic recommendations include the application of vapor phase drying technology can reduce drying time by 20%, diversifying suppliers for long-term delivery materials by adding 2-3 new vendors, implementing the optional strategy of building Testbay 3 to increase testing capacity by 30%, and reallocating 50% of production to high-value MV/HV transformers, which is projected to increase annual output from 10,080 MVA to 12,983 MVA. The limitation of this study is that no investment calculations were made on the optional strategy of building the new Testbay 3. The scenario implementation recommendations are divided into two stages: (1) Short term, including the implementation of vapor phase drying technology, supplier diversification, and the implementation of effective product portfolio reallocation, and (2) Optional strategy including the construction of Testbay 3 taking into account the strategic evaluation of scenario 1.